HISTOCHEMICAL ANALYSIS OF STROMAL MUCIN: A COMPARATIVE STUDY ACROSS GRADED STAGES OF ORAL EPITHELIAL DYSPLASIA AND ORAL SQUAMOUS CELL CARCINOMA - Dr. Maumita Bhattacharya; Dr. Surajit Bose; Dr. Rakshith Shetty; Dr. Subhalakshmi Sen; Dr. Debdita Banerjee; Dr. Arka Das (The Bioscan, 2025)
Background: Mucins are key stromal glycoproteins whose alterations play a role in oral carcinogenesis. Evaluating their distribution may provide insights into the progression from Oral Epithelial Dysplasia (OED) to Oral Squamous Cell Carcinoma (OSCC). Aim: To compare stromal mucin expression in various grades of OED and OSCC using Haematoxylin & Eosin (H&E) and Periodic Acid-Schiff (PAS) stains. Materials and Methods: Fifty histopathologically confirmed cases (25 OED, 25 OSCC) and 10 salivary acini controls were studied. Sections (4 μm) were stained with H&E and PAS. Mucin distribution, staining pattern, and intensity were analysed in 10 fields per case. Results: Results revealed a progressive decline in acid mucin expression from mild to severe OED, with weak and focal positivity in OSCC. Conversely, neutral mucins demonstrated a gradual increase in intensity from OED to OSCC, particularly around tumour islands, reflecting extracellular matrix (ECM) remodelling and tumour progression. PAS staining showed higher intensities in dysplasia compared to OSCC, while H&E staining highlighted greater cytological atypia in severe dysplasia and well-differentiated OSCC. Conclusion: These findings suggest dynamic shifts in mucin profiles during oral carcinogenesis, underscoring their potential as histopathological markers for distinguishing pre-invasive and invasive lesions. The study highlights the diagnostic value of mucin histochemistry in understanding tumour progression and provides a cost-effective adjunct to advanced molecular techniques.